RESPON PERTUMBUHAN DAN KETERGANTUNGAN Albizzia saponaria (LOUR.) MIQ TERHADAP INOKULASI FUNGI MIKORIZA ARBUSKULA LOKAL SULAWESI TENGGARA PADA MEDIA TANAH PASCA TAMBANG NIKEL - Faisal Danu Tuheteru; Husna Husna; Asrianti Arif (BERITA BIOLOGI, 2011)
This study that so far has not been conducted yet by others, regarding the effect of a local AMF species from Southeast Sulawesi on the growth of Albizzia saponaria (Lour.) Miq. The effect of AMF to the plant growth depends on the compatibility between host plant and fungi species which was controlled by genotypes of the both symbionts. The aim of this research is to know the growth respons and dependency of A. saponaria to this local AMF grown in post-nickel mining soil. This research was conducted in the Screen House of Forestry Department, Faculty of Agriculture-Haluoleo University since June to September 2010. A completely randomized design with three replications was used. The treatments were no inoculation of AMF (A), inoculated with -1 -1AMF Mycofer inoculum 5 g polybag (B), and inoculated with local AMF inoculum 10 g polybag (C). The seedling parameter observed were height, diameter, number of leaf, total biomass, number of nodule, percentage of root colonization and relative -1 mycorrhizal dependency (RMD). Results showed the increasing growth and biomass with the application of AMF 10 g polybag (C). There was a positive-strongest correlation value (P<0.01) between percentage of root colonization to all of seedling growth parameters, except to the diameter which was only strong correlated (P<0.05). A. saponaria seedling has high dependency level on local AMF for their survival in heavy metal contaminant soil.